Carrying the Cross of Discord: Sharing and Claims of the Cult of Saint Vladimir of Dioclea/Jovan Vladimir in Contemporary Montenegro - Mammarella, Massimo (Fieldwork in Religion, 2024)
This article investigates the traditional procession of the cross of Vladimir of Dioclea, known as Jovan Vladimir among the Serbians. The ritual is annually held on Trinity Day in June near the city of Bar in Montenegro. Vladimir ruled over the Principality of Dioclea at the beginning of the eleventh century and is venerated as the first Serbian as well as the first Montenegrin saint. Orthodox pilgrims had been carrying the cross up to Mount Rumija for centuries alongside the Catholic and Muslim communities of southern coastal Montenegro, where the saint’s relic has been equally respected by all confessions. After being discouraged by socialist Jugoslav authorities, the ritual was fully restored in the 1990s. However, in 2005 a metal church was erected on the peak of the mountain by the Serbian Orthodox Church, recalling the myth of an old church demolished by the Ottomans in the sixteenth century. This unilateral action induced the other groups to give up the ritual. The dispute over the legitimacy of the metal church in Rumija reveals forms of conflict, negotiation and interaction that redefine the inter-religious and political landscape of Montenegro. Based on fieldwork conducted in 2022 and in 2023, this article pays specific attention to the nationalistic discourse pervading the cult, the myth, and the ritual of Saint Vladimir. It reflects on the attitude of both Serbian Orthodox clerics and believers towards this important procession, but also the volatile degree of inter-religious (in)tolerance.